Diagnostic Arthroscopy of the Minipig Stifle (Knee) for Translational Large Animal Research - Wang, Dean (Arthrosc Tech, 2021)
To gain regulatory approval for the clinical use of knee biologics and devices in humans, translational large-animal studies are typically required. Animal models that permit second-look arthroscopy are valuable because they allow for longitudinal assessment of the treated tissue without needing to sacrifice the animal. The minipig is an ideal preclinical animal model for the investigation of therapies for the knee, in part because arthroscopy can be performed in its stifle (knee) joint with the use of standard surgical equipment used in humans. The purpose of this Technical Note is to describe a reproducible technique for diagnostic arthroscopy of the minipig stifle (knee) joint.